Dexmedetomidine attenuates renal ischemia–reperfusion injury through activating PI3K/Akt‐eNOS signaling via α2 adrenoreceptors in renal microvascular endothelial cells. Issue 11 (17th October 2022) - Shan, Xisheng; Zhang, Jiaxin; Wei, Xiang; Tao, Wenhui; Peng, Ke; Liu, Huayue; Wang, Yiqing; Liu, Hong; Meng, Xiaowen; Ji, Fuhai
Abstract: Renal microvascular endothelial cells (RMECs), which are closely related to regulation of vascular reactivity and modulation of inflammation, play a crucial role in the process of renal ischemia and reperfusion (I/R) injury. Previous studies have reported the protective effects of dexmedetomidine (DEX) against renal I/R injury, but little is known about the role of DEX on RMECs. This study aimed to investigate whether DEX alleviated renal I/R injury via acting on the RMECs. Mice underwent bilateral renal artery clamping for 45 min followed by reperfusion for 48 h, and the cultured neonatal mice RMECs were subjected to hypoxia for 1 h followed by reoxygenation (H/R) for 24 h. The results suggest that DEX alleviated renal I/R injury in vivo and improved cell viability of RMECs during H/R injury in vitro. Gene sequencing revealed that the PI3K/Akt was the top enriched signaling pathway and the endothelial cells were widely involved in renal I/R injury. DEX activated phosphorylation of PI3K and Akt, increased eNOS expression, and attenuated inflammatory responses. In addition, the results confirmed the distribution of α2 adrenoreceptor (α2 ‐AR) in RMECs. Furthermore, the protective effects of DEX against renal I/R injury were abolished by α2 ‐AR antagonist (atipamezole), which was partly reversed by the PI3K agonist (740 Y‐P). These findings indicated that DEX protects against renal I/R injury by activating the PI3K/Akt‐eNOS pathway and inhibiting inflammation responses via α2 ‐AR in RMECs.